Impact of Orlistat-Induced Weight Loss on Diastolic Function and Heart Rate Variability in Severely Obese Subjects with Diabetes. (2nd December 2010) - Martin, Julie; Paquette, Carmen; Marceau, Simon; Hould, Frédéric-Simon; Lebel, Stéfane; Simard, Serge; Dumesnil, Jean-Gaston; Poirier, Paul
Abstract : Objective . Determine the impact of Orlistat-induced weight loss on metabolic profile and cardiovascular function in severely obese patients with type 2 diabetes. Methods . Twenty-nine patients were randomized either to a nonplacebo control group or to a treatment group with Orlistat thrice a day. Metabolic profile, anthropometric parameters, heart rate variability indices, and echocardiographic variables were measured before and after a 12-week treatment period. Results . Treatment with Orlistat induced a modest but significant weight loss compared to controls (3.7 ± 3.0 versus 0.5 ± 2.2 kg, resp.;P = .003 ). There was significant decrease in fasting glycemia (7.9 ± 3.0 versus 6.7 ± 2.2 mmol/L;P = .03 ) and significant improvements in left ventricular diastolic function (P = .03 ) and in the sympathovagal balance (LF/HF ratio) (P = .04 ) in the Orlistat group. Conclusion . These results suggest that a modest weight loss improves fasting glycemia, left ventricular diastolic function, and sympathovagal balance in severely obese patients with type 2 diabetes.